General aspects of laboratory techniques for the diagnosis of COVID-19 - Pinto, Geise Raquel Sousa Pinto (2020)
SARS-CoV-2 is a new virus of unknown origin that appeared in China in December 2019. The diagnosis is complex and involves the need to understand the types of tests and their peculiarities. There are two diagnostic tests available at the moment: the molecular and the immunological (also called serological). Each has its own specific characteristics. Given this context, the present study aimed to describe the general aspects of the techniques used in the diagnosis of COVID-19. This is a descriptive bibliographic review study with a quantitative approach in the databases of Scielo, Lilacs, Google Scholar and through the Research Portal of the Virtual Health Library (VHL). The sensitivity of tests for the detection of antibodies by different techniques varied between 81.5% and 88.6%, and specificity varied between 90.6% and 100%. Studies evaluating the sensitivity of RT-PCR in relation to diagnostic criteria identified sensitivity of 44.2% for samples collected by oropharyngeal swab and 76.9% when the sample used was sputum. The assessment of the diagnostic accuracy of viral particle amplification tests applied in the point-of-care modality showed a sensitivity of 90% and specificity of 100%, in relation to RT-PCR. Serological tests seem to have good sensitivity and specificity when applied at a later stage of the infection. In the early stages of infection, they have a high rate of false negative results. However, to date, the RT-PCR test is indicated for the definitive diagnosis of COVID-19.